Recent Progress and Future Challenges in MR Electric Properties Tomography - Katscher, Ulrich (Hindawi Publishing Corporation, 2013)
MR Electric Properties Tomography (EPT) is a lately developed medical imaging modality capable of visualizing both conductivity and permittivity of the patient at the Larmor frequency using B (1) maps. The paper discusses the development of EPT reconstructions, EPT sequences, EPT experiments, and challenging issues of EPT.